Strategic nonlinear income tax competition with perfect labor mobility - Felix Bierbrauer; Craig Brett; John A. Weymark (Center for Economic Studies and ifo Institute (CESifo), 2011)
Tax competition between two governments who choose nonlinear income tax schedules to maximize the average utility of its residents when skills are unobservable and labor is perfectly mobile is examined. We show that there are no Nash equilibria in which there is a skill type that pays positive taxes to one country and whose utility is larger than the average utility in the other country or in which the lowest skilled are subsidized. We also show that it is possible for the most highly skilled to receive a net transfer funded by taxes on lower skilled individuals in equilibrium. These findings confirm the race-to-the-bottom thesis in this setting.
Keywords: D82; H21; H87; 330; income tax competition; labor mobility; optimal income taxation; race to the bottom; Einkommensteuer; Steuerwettbewerb; Hochqualifizierte Arbeitskräfte; Internationale Arbeitsmobilität; Optimale Besteuerung; Theorie